Antimicrobial properties of composites of chitosan-silver doped zeolites - Scacchetti, Fabio A. P. (2020)
The antimicrobial functionality of composites constituted by chitosan with silver-doped zeolites was developed and characterized. A composite with chitosan particles and silver-doped zeolites was synthesized using an ionic gelation process with sodium tripolyphosphate. The chitosan silver-doped zeolites composite obtained presented sizes up to 5 mu m, while the silver-doped zeolites had an average size between 0.5 mu m and 3.3 mu m. The synthesized chitosan silver-doped zeolites composites, as well as the silver-doped zeolites and the chitosan dissolution, were characterized through X-ray diffraction, Fourier Transform Infrared spectroscopy and scanning electron microscopy. The electro kinetic behaviour of chitosan, silver-doped zeolites and chitosan silver-doped zeolites composite was evaluated under different pH conditions. The antimicrobial activity of the composites was evaluated in terms of minimum inhibitory concentrations and minimum lethal concentrations and the results suggest that the chitosan silver-doped zeolites composites show antimicrobial activity against gram-negative and gram-positive bacteria, Escherichia coli and Staphylococcus aureus, respectively and against Candida albicans. The results here presented support the potential application of the composite of chitosan with silver-doped zeolites in the functionalization of textiles with antimicrobial properties.